Transformasi Sumber Daya Manusia Pada Lembaga Pendidikan Dalam Upaya Meningkatkan Kualitas dan Kinerja - lidya Fitri; Jamilus (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Human resource transformation in educational institutions is a strategic step taken to enhance the quality and performance of the institution in response to evolving changes. In an ever-changing education landscape, human resources play a crucial role in creating an optimal learning environment and effectively meeting the needs of students. This article highlights the importance of human resource transformation in educational institutions and the impact it can have when implemented successfully. The transformation of human resources encompasses various aspects, ranging from recruitment, selection, development, to performance management. Educational institutions need to employ effective strategies to recruit qualified individuals who are committed to delivering quality education to students. Additionally, careful selection is essential to ensure that candidates possess the necessary qualifications aligned with the institution's needs. Performance management is another critical aspect to consider in human resource transformation. Educational institutions should have transparent and continuous performance evaluation systems to assess individual performance and provide constructive feedback. By ensuring objective performance assessments and providing appropriate support, educational institutions can encourage educators and staff to enhance the quality of teaching and educational services overall. This article presents the concepts and benefits of human resource transformation in educational institutions, offering guidance for institutions to adopt best practices and drive sustainable changes to improve the quality and performance of the institution.